2018
DOI: 10.1080/20008198.2018.1450595
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in trauma-exposed youth: a meta-analysis

Abstract: An earlier meta-analysis and review indicated that trauma exposure may be related to lower levels of executive functioning in youth. Since different developmental trajectories were found for three core executive functions, the present study focused on working memory, inhibition, and cognitive flexibility specifically. We conducted a multi-level meta-analysis on 55 studies and 322 effect sizes published between 2001 and 2017 that were retrieved from MEDLINE, Embase, and PsycINFO. The 8070 participants in select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 61 publications
5
33
0
1
Order By: Relevance
“…Maltreatment leads to serious problems in children’s psychosocial functioning. It has shown to be associated with lower executive functioning, which negatively influences behaviour in daily life (Op den Kelder, Van den Akker, Geurts, Lindauer, & Overbeek, 2018 ). Experiences of childhood trauma also have a negative impact on the developing stress regulatory system of the brain, resulting in children’s difficulty to regulate their emotions (Burkholder, Koss, Hostinar, Johnson, & Gunnar, 2016 ; Kim & Cicchetti, 2010 ; Perry, Runyan, & Sturges, 1998 ).…”
Section: Evaluation Of the Training For Foster Parents ‘Caring For Chmentioning
confidence: 99%
“…Maltreatment leads to serious problems in children’s psychosocial functioning. It has shown to be associated with lower executive functioning, which negatively influences behaviour in daily life (Op den Kelder, Van den Akker, Geurts, Lindauer, & Overbeek, 2018 ). Experiences of childhood trauma also have a negative impact on the developing stress regulatory system of the brain, resulting in children’s difficulty to regulate their emotions (Burkholder, Koss, Hostinar, Johnson, & Gunnar, 2016 ; Kim & Cicchetti, 2010 ; Perry, Runyan, & Sturges, 1998 ).…”
Section: Evaluation Of the Training For Foster Parents ‘Caring For Chmentioning
confidence: 99%
“…Taken together, these findings suggest that salient visuospatial sensory information, guided, in part, by oculomotion, informs perspective on the relevance of incoming sensory input. Previous studies have indicated that eye movements performed simultaneously with episodic memory retrieval tax working memory resources; such interference may reduce the capacity to engage in other higher order tasks reliant upon executive functioning (Maxfield, Melnyk, & Hayman, 2008;Op den Kelder, Van den Akker, Geurts, Lindauer, & Overbeek, 2018).…”
Section: Dorsal Attentional Networkmentioning
confidence: 99%
“…Traumatic experiences and PTSS have both been associated with reduced cognitive functioning relative to performance in healthy control (S. Malarbi et al, 2017;Scott et al, 2015), with potential consequences for everyday functioning (Biederman et al, 2004;Danzi & La Greca, 2017). One of the cognitive domains that appear to be most affected is executive functions (B. C. Kavanaugh et al, 2017;Op den Kelder et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews (B. C. Kavanaugh et al, 2017;Pechtel & Pizzagalli, 2011;Perkins & Graham-Bermann, 2012) and meta-analyses (S. Malarbi et al, 2017;Op den Kelder et al, 2018) have focused on associations between early-life stress or trauma exposure and functioning in different cognitive domains in children and adolescents. Instead, we chose to focus on cognitive functioning in children and adolescents with PTSS, rather than on groups with reported experienced traumatic events.…”
Section: Introductionmentioning
confidence: 99%